Multimedia Cerdas Untuk Generasi Masa Depan: Tren dan Teknologi Terbaru - Rani Fira Yunita; Tata Sutabri (Router : Jurnal Teknik Informatika dan Terapan, 2024)
The development of intelligent multimedia technology has had a significant impact on various sectors, especially in education, social, and cultural fields. This article discusses the latest trends in the use of intelligent multimedia and related technologies such as Artificial Intelligence (AI), Internet of Things (IoT), and Virtual Reality (VR), which have transformed the way we learn and interact with the world around us. In the context of education, intelligent multimedia enables a more personalized and adaptive approach to students' needs, enhancing educational accessibility, and reducing the educational gap between urban and rural areas. This technology also contributes greatly to creating a more interactive and engaging learning environment. On the other hand, the use of intelligent multimedia in social and cultural fields opens up opportunities to enrich local identities in the face of globalization, by incorporating traditional cultural elements into technology-based product designs. However, despite its many benefits, the implementation of intelligent multimedia technologies faces various challenges, such as infrastructure issues, limited budgets, and resistance from some educators who are not yet familiar with new technologies. Therefore, it is essential to ensure adequate digital literacy so that future generations can fully utilize this technology responsibly. In conclusion, intelligent multimedia has great potential to improve the quality of life, but its application must be carried out wisely, taking into account long-term impacts on society and culture.